Espaço vivido e espaço mental: Dalton Trevisan e a dicotomia social do urbanismo curitibano - Nelson H. Vieira (Universidade de Brasília, 2013)
This essay deals with the short stories of Dalton Trevisan and the city of Curitiba within the context of urbanism as “lived space”, using André Lefebvre’s terminology, with the aim of understanding the social dichotomy between a rural mentality and an urban modernity. By contrasting the many praises that Curitiba has received as a “green city” with tragic-comic and ominous scenarios played out in Trevisan’s narratives, this study points to the socio-historic vestiges of its past as a colonial city and how that social experience still marks local behavior. Besides illustrating how Trevisan’s short stories tend toward the universal, due to their highly conscious dialog with the reader and in spite of its regional focus, we underscore how the contradiction between the sardonic and the affective uncovers the sentimental yet disturbing side of this Human Comedy. With allusions to his stories and haikus as “thinking images” (coined by Walter Benjamin), this reading also emphasizes the performative aspect of his work that serves to unmask the hidden hypocrisy within the urban consciences of his protagonists and those of his readers. In opposition to the mental space formulated by urban planners, one sees how “space lived” by its inhabitants does not tie well into the highly promulgated ecological image of the city. However, in the midst of the city’s vampiresque evocation emanating from the author himself, there always emerges a dose of compassion and nostalgia which in the final analysis challenges Dalton Trevisan’s image as a mordant and insensitive critic of his Curitiba.